Wniebowzięci - Kondratiuk, Andrzej (Poland : Zespoły Filmowe Pryzmat, 1972)
A comedy of manners. Two middle-aged men win the lottery and decide to spend the proceeds on flying in an airplanes for the first time in their lives. Having tried the taste of air travel, they waste the money on more – domestic – flights. In an airport restaurant in Rzeszów, they meet two local girls and take them on a flight to Gdańsk. There, they book two hotel rooms, and evidently wanting to carry on with the party. The girls are reluctant, though, and lock themselves in their room. They come back feeling of unfulfilled and conclude that pretending to be somebody else will not make them any happier. The film seems to be a quasi-documentary, as Kondratiuk employs non-professional actors and the dialogues seem to be improvised on the spot.
Duration: 00:44:00
Keywords: Poland